2022
DOI: 10.3390/ijerph192315788
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychological Flexibility and Children’s Behavior Problems in Rural Areas in Northeast China: The Mediation of Children’s Emotion Regulation

Abstract: Children’s behavior problems are not conducive to their sustainable development. Therefore, it is of great value to explore the mechanism of relevant influencing factors on the behavior problems of rural preschoolers. This study aimed to reveal the direct effect of parental psychological flexibility on children’s behavior problems and the mediating effect of children’s emotion regulation. Based on simple random sampling, 355 caregivers (male = 31.25 years, SD = 9.78; 74.08% females; 9.01% bachelor degree) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…Its role in moderating the effects of distress-driven impulsivity and problematic behaviors (Liu et al, 2022) supports our findings on the predictive value of psychological flexibility for empathy. Additionally, Faulkner et al (2021) and Ren et al (2022) demonstrate how psychological flexibility can impact health outcomes and child development, respectively, through mechanisms such as emotion regulation (Faulkner et al, 2021;Ren et al, 2022). This study's findings, situated within the broader research landscape, underscore the importance of considering the dynamic interplay between empathy, impulsivity, and psychological flexibility.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Its role in moderating the effects of distress-driven impulsivity and problematic behaviors (Liu et al, 2022) supports our findings on the predictive value of psychological flexibility for empathy. Additionally, Faulkner et al (2021) and Ren et al (2022) demonstrate how psychological flexibility can impact health outcomes and child development, respectively, through mechanisms such as emotion regulation (Faulkner et al, 2021;Ren et al, 2022). This study's findings, situated within the broader research landscape, underscore the importance of considering the dynamic interplay between empathy, impulsivity, and psychological flexibility.…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown to impact the relationship between psychological factors like rumination and impulsivity and health outcomes such as psychological distress (Faulkner et al, 2021). Additionally, parental psychological flexibility has been found to affect children's behavior problems through the mediation of children's emotion regulation (Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multiple studies have found that parents' parenting psychological exibility has a signi cant positive impact on children's behavioral problems and psychological development. A study involving parents of rural Chinese preschoolers found that parents' psychological exibility negatively predicts their children's internalizing and externalizing problems 30 . Low levels of parenting psychological exibility increase the risk of emotional, behavioral, and peer problems in children, while high parenting psychological exibility reduces the frequency of children's problem behaviors 31 .…”
Section: The Mediating Role Of Parenting Psychological Exibilitymentioning
confidence: 99%
“…Gross y Thompson (2007) definen la regulación emocional como aquellos procesos por los que las personas ejercen influencia sobre su estado emocional, que involucra un intento de regular desde qué emociones tener, cuándo sentirlas, cómo experimentarlas y hasta cómo expresarlas. Algunas conceptualizaciones sobre la regulación emocional (o la desregulación) ponen el acento en el control sobre la experiencia subjetiva y la expresión emocional (Ren et al, 2022), mientras que otras enfatizan en la función de las emociones y señalan que regulación y control no son conceptos intercambiables (Cole et al, 1994). Adicionalmente, otros autores han destacado las estrategias utilizadas para regular las emociones, considerando algunas de estas adaptativas y otras desadaptativas (Boemo et al, 2022).…”
Section: Introductionunclassified